Kenne, denke en openbaring in die (regs -)wetenskap volgens die wsbegeerte van die skeppingsidee - Raath, A. W. G. (Koers, 1986)
In this article the role of knowledge, thought and revelation in (jural-)science, according to the Philosophy of the Idea of Creation, is subjected to a critical analyses. It is concluded that, firstly the so-called method of Wesenschau is used b y all branches of Calvinistic philosophy to reveal the modal kernel of the jural law-sphere . Them ethodological approach of H . J . van Eikem a Hommes clearly illustrates this . Secondly it is concluded that H.G. Stoker awards the correct position to knowledge, thought and revelation in his philosophy. The emphasis on human thought is a legacy of Humanistic theories of know ledge.